PREVALENCE AND RISK FACTOR OF HAEMONCHUS CONTORTUS IN LAKOR GOAT IN LAKOR DISTRICT SOUTHWEST MALUKU - Sukariada, I Putu Juli; Ludji, Sherli Melani; Noach, Steffanie M. C.; Puspitayani, Putu Mira (Universitas Syiah Kuala, 2024)
The aimed of this research is to determine the prevalence of Haemonchus. contortus and the associated risk factors. In this study, 739 fecal samples from Lakor goats were randomly collected from five villages in Lakor District, Southwest Maluku. All samples were taken from goats showing clinical symptoms such as emaciation, diarrhea, dull fur, and inactive. Fecal samples were examined using the native method. Data presentation was analysed using the Chi-Square (X2) and Spearman's test statistical analysis methods. The prevalence of H. contortus in Lakor goats in the Lakor sub-District was 81.60% with the highest prevalence was found in Yamluli Village and Lolotuara Village. The correlation coefficient was 0.838** - 0.931** (P0.01). These data indicated that there is a close relationship between the incidence of H. contortus worm infection in lakor goats and the risk factors in the form of gender, age of the goat and body score condition (BCS) as indicated by the high correlation values.